Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Toleransi Beragama Peserta Didik di SMK Negeri 1 Pangkalpinang - Rahayu, Dea Putri; Zayadi, Zayadi; Jauhari, Muhammad Insan (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The background of this study is the researcher's view regarding the many cases of intolerance circulating which cause students to behave intolerantly, while what the researcher saw and observed when conducting observations at school stated that students had behaved tolerantly so that the researcher's concern is related to the role of Islamic Religious Education (PAI) teachers so that good religious tolerance emerges at SMK Negeri 1 Pangkalpinang. This study aims (1) To find out and describe the role of Islamic Religious Education (PAI) teachers as educators, teachers, mentors, trainers, advisors, innovators, models and role models and individuals in instilling the values ​​of religious tolerance in students (2) To find out and describe how the values ​​of religious tolerance are instilled in students at SMK Negeri 1 Pangkalpinang. This study is a type of qualitative research with a case study approach. The data collection techniques used are interviews, observation, and documentation. The data analysis techniques include data reduction, data presentation (data display), and verification (drawing conclusions). The results of the study can be concluded that: Islamic Religious Education (PAI) teachers have played a role in instilling the values ​​of religious tolerance, including teachers as educators, teachers, mentors, trainers, advisors, innovators, models and role models, and as individuals. Instilling the values ​​of religious tolerance, namely the values ​​of inclusive diversity in the form of understanding religious tolerance, 3S culture (smile, greet, say hello), respecting and honoring each other's beliefs, humanism values ​​including helping each other, social assistance, group activities, P5, extracurricular activities and routine school activities, and the values ​​of freedom including the freedom to embrace and believe in each religion and channel talents according to the abilities of each individual student.